Genetic testing in the diagnosis of chronic kidney disease: recommendations for clinical practice - Knoers, Nine; Antignac, Corinne; Bergmann, Carsten; Dahan, Karin; Giglio, Sabrina; Heidet, Laurence; Lipska-Ziętkiewicz, Beata S.; Noris, Marina; Remuzzi, Giuseppe; Vargas-Poussou, Rosa; Schaefer, Franz (Nephrology, dialysis, transplantation, 2022)
The overall diagnostic yield of massively parallel sequencing-based tests in patients with chronic kidney disease (CKD) is 30% for paediatric cases and 6-30% for adult cases. These figures should encourage nephrologists to frequently use genetic testing as a diagnostic means for their patients. However, in reality, several barriers appear to hinder the implementation of massively parallel sequencing-based diagnostics in routine clinical practice. In this article we aim to support the nephrologist to overcome these barriers. After a detailed discussion of the general items that are important to genetic testing in nephrology, namely genetic testing modalities and their indications, clinical information needed for high-quality interpretation of genetic tests, the clinical benefit of genetic testing and genetic counselling, we describe each of these items more specifically for the different groups of genetic kidney diseases and for CKD of unknown origin.
Published 15 July 2021
Gesehen am 29.03.2022